Radomizing an Antenna for a SAR-Based ETA Radar System While Ensuring Imaging Accuracy: A Focus on Phase Shifts - María Elena de Cos Gómez; Alicia Flórez Berdasco; Jaime Laviada Martínez; Fernando Las-Heras Andrés (Micromachines)
The impact of radomization on the radiation pattern of a millimeter-wave antenna for an ETA system utilizing synthetic aperture radar (SAR) is examined with special emphasis placed on the phase shift across both the beamwidth and the bandwidth, rather than the amplitude. Three different radomization approaches, including one based on metasurfaces, are evaluated for a radar antenna operating within the 24.05–24.25 GHz frequency range. Fabricated prototypes, both of the standalone antenna and the radomized version, are tested and compared in terms of electromagnetic image quality. The metasurface-based radome provides the best results among the radomization options analyzed.